Designing a Gamification Model Based on Customer Engagement Indicators to Increase Loyalty and Revenue in Small and Medium-Sized Online Businesses - Saeed Gullshenas , Mohammad; Akbarpour Shirazi, Mohsen (Digital Transformation and Administration Innovation, 2026)
This study aimed to design and empirically test a gamification model based on customer engagement indicators to enhance customer loyalty and improve business performance in small and medium-sized online businesses. A mixed-methods research design was employed, combining qualitative and quantitative approaches. In the qualitative phase, semi-structured interviews were conducted with 12 experts in digital marketing, user experience design, and online business management to identify key gamification components and mechanisms. Data were analyzed using thematic analysis with open, axial, and selective coding. In the quantitative phase, a researcher-developed questionnaire, informed by the qualitative findings and theoretical literature, was distributed to 384 active customers of Iranian online businesses who interacted with gamified elements through e-commerce platforms. Convenience sampling was used, and data were analyzed using SmartPLS 3.2 for confirmatory factor analysis, structural equation modeling (SEM), and model fit assessment. Inferential analysis showed that gamification had a significant positive effect on customer engagement (β = 0.72, t = 12.58, p < 0.001) and that customer engagement significantly influenced customer loyalty (β = 0.69, t = 11.76, p < 0.001). Gamification also had a direct positive effect on loyalty (β = 0.34, t = 6.32, p < 0.001), with a substantial total effect (β = 0.83, t = 15.89, p < 0.001). R² values indicated that gamification explained 52% of the variance in engagement and, with engagement, 61% of the variance in loyalty. The Q² value (0.440) demonstrated strong predictive relevance, and model fit indices (SRMR = 0.068; GoF = 0.470) confirmed good model adequacy. Gamification is an effective strategy for increasing customer engagement and loyalty in small and medium-sized online businesses, with engagement serving as a partial mediator in the gamification–loyalty relationship. These findings support the integration of gamification into SME digital marketing strategies to strengthen customer relationships and enhance performance outcomes.